On the Along‐Slope Heat Loss of the Boundary Current in the Eastern Arctic Ocean. Issue 2 (15th February 2021) - Schulz, Kirstin; Janout, Markus; Lenn, Yueng‐Djern; Ruiz‐Castillo, Eugenio; Polyakov, Igor; Mohrholz, Volker; Tippenhauer, Sandra; Reeve, Krissy Anne; Hölemann, Jens; Rabe, Benjamin; Vredenborg, Myriel
Abstract: This study presents recent observations to quantify oceanic heat fluxes along the continental slope of the Eurasian part of the Arctic Ocean, in order to understand the dominant processes leading to the observed along‐track heat loss of the Arctic Boundary Current (ABC). We investigate the fate of warm Atlantic Water (AW) along the Arctic Ocean continental margin of the Siberian Seas based on 11 cross‐slope conductivity, temperature, depth transects and direct heat flux estimates from microstructure profiles obtained in summer 2018. The ABC loses on average O (10 8 ) J m −2 per 100 km during its propagation along the Siberian shelves, corresponding to an average heat flux of 47 W m −2 out of the AW layer. The measured vertical heat flux on the upper AW interface of on average 10 W m −2 in the deep basin, and 3.7 W m −2 above the continental slope is larger than previously reported values. Still, these heat fluxes explain less than 20% of the observed heat loss within the boundary current. Heat fluxes are significantly increased in the turbulent near‐bottom layer, where AW intersects the continental slope, and at the lee side of a topographic irregularity. This indicates that mixing with ambient colder water along the continental margins is an important contribution to AW heat loss. Furthermore, the cold halocline layer receives approximately the same amount of heat due to upward mixing from the AW, compared to heat input from the summer‐warmed surface layer above. This underlines the importance of both surface warming and increased vertical mixing in a future ice‐free Arctic Ocean in summer. Plain Language Summary: Warm water from the Atlantic Ocean enters the Arctic Ocean through the Barents Sea and the Fram Strait, between Greenland and Norway, and directly influences the formation of sea ice: When the Atlantic Water (AW) is located close to the ocean's surface, as is the case shortly after its inflow in the Barents Sea, sea ice melts and new sea ice formation is hindered. This is why the Barents Sea is often ice free, even in winter. Further along the pathway, in the Laptev and East Siberian Sea study region, the AW gradually cools and dives down to deeper layers. In order to quantify the cooling and to understand how and where it happens, we measured vertical profiles of temperature and heat fluxes along a 2, 500 km long part of the AW pathway. Based on these measurements, we found that the heat loss mainly occurs by mixing of warm AW with ambient cold water above the continental slope, in particular in the highly energetic region near the sea floor. Key Points: The Atlantic Water (AW) transported in the Arctic Boundary Current loses O (10 8 )  J m −2 per 100 km during its translation along the Siberian shelves Heat fluxes are larger than previously reported values, but too small to account for this heat loss, indicating the importance of boundary mixing The heat input from the underlying AW layer to the cold halocline is of similar magnitude to the heat input from the warm surface layer above